Pengaruh Perbandingan Mocaf Dengan Tepung Daun Papasan (Coccinia Grandis) Terhadap Karakteristik Kue Stik - Ayu Puspitayanti, Ni Kadek; Ari Yusasrini, Ni Luh; Ekawati, I Gusti Ayu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 2 (2021): Jurnal ITEPA, 2021)
This study aims to determine the effect of mocaf comparison with papasan leaf flour on the characteristics of stick cake and to find out the proper mocaf comparison with papasan leaf flour so as to produce the best stick cake characteristics. The Completely Randomized Design (CRD) was used a with the treatment of mocaf comparison and papasan leaf flour which consists of 5 levels, namely: 100% mocaf: 0% papasan leaf flour, 95% mocaf: 5% papasan leaf flour, 90% mocaf: 10 % papasan leaf flour, 85% mocaf: 15% papasan leaf flour, and 80% mocaf: 20% papasan leaf flour. The research data were analyzed of variance (ANOVA) and if the treatment had a significant effect it was continued with Duncan's Multiple Range Test (DMRT). The results showed that the comparison of mocaf and papasan leaf flour to the resulting sticks had a very significant effect on water content, ash content, antioxidant activity, total chlorophyll, calcium levels, breaking strength of cake sticks and sensory properties including texture, taste, color, aroma , and overall acceptance. The best characteristics produced in the treatment of 95% mocaf: 5% papasan leaf flour that produces a water content of 1.70%, ash content of 4.24%, antioxidant activity of 11.39%, total chlorophyll content of 89.52 mg / L , calcium content of 238.73 mg /g, fracture power of 13.07 N, and sensory characteristics include greenish brown color and like, aroma like, taste rather typical of papasan leaves and very like, crispy and like texture, overall acceptance of likes.